Patient with suspected co-infection of hemorrhagic fever with renal syndrome and malaria: a case report - Zhao, Han-Dong; Qian, Hong-Bo; Wang, Ze-Kun; Ren, Rui-Kang; Yu, Tong-Bo; Liu, Hong-Li (Frontiers in Medicine, 2024)
Background Hemorrhagic fever with renal syndrome (HFRS) is a natural epidemic disease that can be caused by the Hantaan virus (HTNV). Malaria is caused by plasmodium and can be transmitted by a mosquito bite. The similar manifestations shared by these disorders pose a challenge for clinicians in differential diagnosis, in particular, coupled with a false-positive serological test. Case presentation A 46-year-old man was admitted for fever and chills for over 10 days and was suspected of being co-infected with HFRS and malaria due to a history of travel to malaria-endemic areas and a positive HTNV-immunoglobulin M (IgM) test. Although leukocytosis, thrombocytopenia, renal injury, lymphocytosis, overexpression of interleukin-6, and procalcitonin were observed during the hospitalization, the hypotensive, oliguria, and polyuria phases of the HFRS course were not observed. Instead, typical symptoms of malaria were found, including a progressive decrease in erythrocytes and hemoglobin levels with signs of anemia. Furthermore, because the patient had no history of exposure to HFRS endemic areas, exposure to an HTNV-infected rodent, or a positive HTNV-IgG test, and false serological tests of IgM can be caused by various factors, the HFRS coinfection with malaria was ruled out. Conclusion Misdiagnosis can be easily induced by a false serological test, in particular the IgM test which can be influenced by various factors. A combination of health history, epidemiology, physical examination, precise application of specific examinations involving tests of conventional laboratory parameters as well as well-accepted methods such as the immunochromatographic (ICG) test, real-time reverse transcription-polymerase chain reaction (PCR), and Western blot (WB), and acquaintance with disorders with similar manifestations will contribute to the precise diagnosis in clinical treatment.